Um ambiente virtual de aprendizagem para o ensino de tópicos de matemática do ensino fundamental - Abbondati, Mario (Universidade Federal de São Carlos, 2012)
The objective of this work was the development and application of a Virtual Learning Environment (VLE), based on the Moodle platform, for the study of Mathematic topics at the elementary education level. Furthermore, another purpose is to observe the student's work within this environment and, subsequently, the analysis of the results of this proposed teaching method. The VLE concept was developed with the ISMART foundation students in mind, which are studying at the Bandeirantes School, in Sao Paulo. This foundation is a nonprofit organization that grants scholarships to academically well performing students as well as those of low income families, which are selected through exams and interviews. The selected themes within VLE are quantities and also measurements, chosen for their importance and relevance in every-day life, divided into four units: Measurements of Length, Surface, Volume and Percentage. Emphasis is given to the concept of measurement, by studying the various quantities and diverse approaches, such as: historic, the use of nontraditional unit standards and interactive applications. In relation to the percentage theme, it is important that the students familiarize themselves with different representation of rational numbers (fraction, decimal and percentage). Besides that, this theme is part of the everyday information, where we are dealing with spreadsheets, graphics and statistic data. As part of the VLE, it was the intention of this study to seek real life problems that would involve the use of calculators for more complicated calculations. Furthermore, mental percentage calculations were practiced by applying a specially developed game. Resources were utilized in form of texts, images, audio, video, flash animations and Geogebra applications, besides PowerPoint exercises that were solved in a step by step method as well as other proposed exercises. The VLE was executed with ISMART students of 2011 and 2012, whereby some activities were developed at the School and others at home.
Keywords: Matemática - estudo e ensino; Ambiente virtual de aprendizagem; Ensino a distância; Plataforma moodle; Grandezas e medidas; Tratamento da informação; Tecnologias de Informação e Comunicação; Ensino Fundamental; Geogebra; Virtual Learning Environment; Distance Education; Moodle; Measurements; Percentage; Information and Communication Technologies; Elementary Education; Geogebra; CIENCIAS EXATAS E DA TERRA::MATEMATICA